PERTUKARAN SOSIAL ANTARA JURAGAN DENGAN BURUH NELAYAN DI DESA MANDAR, KABUPATEN SUMENEP, MADURA - Alfiandi, Rully; Nugroho, Wahyu Budi; Krisna Aditya, I Gst. Agung (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
This study will analyze the social exchange between fishing workers and skippers in Mandar Village, Sumenep Regency, Madura. The research method used is qualitative research. This study uses the exchange theory of George Homans. Social exchanges that occur between fishing workers, namely fishermen workers form a group of fellow fishermen workers, in this group fishing workers exchange information about work. Social exchange between independent fishermen and fish collectors occurs because they need each other, independent fishermen when experiencing difficulties will be assisted by fish collectors which causes independent fishermen to continue to sell their fish to the same fish collectors. Social exchange between fishing workers and fishermen who own capital, namely laborers if they experience difficulties, will be assisted by their bosses so that workers will respond by cleaning and disposing of water from the boats belonging to fishermen who own capital even though it is outside of their job. Keywords: social exchange, fishing labor, skipper.